Armorial Quintet and its relationship with Brazilian modernity (1974-1980) - Santos, Nivea Lins [UNESP] (Univ Federal Uberlandia, 2017)
The Armorial Quintet decided to developin the 1970s a national chamber music based on a fusion of North eastern bush areas (sertao) popular sounds and the canons of traditional European classical culture. According to the Armorial Movement, especially in the view of its mentor Ariano Suassuna, a few elements of modernity had the potential to jeopardize traditional identities. Thus, for the members of the Armorial movement, large recording industries, integrated into the market logics, encouraged a fundamentally commercial style of music and should therefore be problematized. This was one of the reasons for the quintet to approach the Marcus Pereira recording label, which was farther from this logics. Therefore, in this article we wish to discuss how the aesthetic project of the Armorial Quintet was designed, aimed at developing a more artisanal sound material and very close to the national culture proposed by Mario de Andrade, whose ideas, incidentally, were the basis for Ariano Suassuna and Marcus Pereira's thoughts.
Keywords: Rio da Prata; XIXth century; antimodernity